Negotiating LGBTQ rights in Singapore: The margin as a place of refusal - Ramdas, Kamalini (Urban studies (Edinburgh, Scotland), 2021)
The complex diversity of urban life in cities is often the cause of social friction but it can also spark change. Densely populated cities are places where individuals find community but they are also places where some communities become marginalised and excluded. In the city-state of Singapore community-based activism is an important strategy for minority groups claiming a right to their place in the city. Conceptualising the margin as a place of refusal, the paper focuses on how Singapore’s LGBTQ communities have contested and negotiated from their place at the margins of the city-state, calling into question the Singapore State’s hegemonic narratives of family and community for heteronormative nation-building. These contestations have resulted in strategies that both adopt and elide individual rights-based narratives that have centred primarily on the repeal of Section 377A of Singapore’s penal code. While the repeal of 377A remains critical, the paper focuses on three examples of Sayoni’s community advocacy, Pink Dot and education, which extend the discourse beyond the issue of repeal, and the single identity category of sexuality. Even as the fight for repeal continues, LGBTQ subjects are resisting, negotiating and advocating against violence, discrimination and making space for love and community in ways that co-opt and destabilise social norms in Singapore, thus occupying the margin as a place of radical openness. 城市生活的复杂多样性往往是引起社会摩擦的原因，但也可能引发变革。在人口稠密的城市中，个人能找到社群，但也正是在这样的城市中，一些社群遭到边缘化和排斥。在新加坡这个城市国家，以社群为基础的行动主义是少数群体要求在城市中拥有一席之地的重要策略。本文将边缘地带概念化为一个遭受拒绝的地方，重点关注新加坡的男女同性恋/双性恋/变性者和双性人群体 (LGBTQ) 如何从他们所处的城市国家边缘的位置进行竞争和谈判，并质疑新加坡政府基于父权的国家建设所决定的家庭和社区霸权叙事。这些争论导致采取和取消以个人权利为基础的叙述的策略，焦点在于废除新加坡《刑法》第377A条。虽然废除《刑法》第377A条仍然至关重要，但本文重点关注萨约尼 (Sayoni) 社群倡导、粉红点 (Pink Dot) 和教育这三个例子，这些例子将讨论扩展到废除问题、以及单一的性身份类别之外。尽管废除的斗争仍在继续，但LGBTQ群体仍在就反对暴力、歧视问题进行抵制、谈判和倡导，并为爱和社群创造空间（以一种指向并撼动新加坡社会规范的方式），从而占据了边缘地带并使之成为了一个开放的地带。